Inovasi Program Rumah Kreatif Sleman dalam Meningkatkan Daya Saing Usaha Mikro Kecil Menengah - Akbar, M Satrio; Sri Nugroho, Hanantyo; Rahmawati, Agustina (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
This study was conducted to examine the innovation of the Sleman Creative House (RKS) Program in Increasing the competitiveness of micro, small and medium enterprises in Sleman Regency. This study also aims to determine the obstacles, challenges and types of innovations that exist in the Sleman Creative House. This type of research is qualitative research, a descriptive research approach, which emphasizes in depth on a phenomenon, context, and meaning. Data were collected through in-depth interviews with stakeholders, observation and documentation. The theories used to measure the success of innovation in the Sleman Creative House are innovation as an event (Ideas), innovation as a process (deliverable) and innovation as a capability (environment). The research findings show that the Sleman Creative House program has provided various innovations to increase the competitiveness of MSMEs through coaching programs, mentoring classes, sharing classes and practice classes. However, there are still several obstacles and challenges that need to be overcome, such as the problem of limited coaches, limited access to information, different levels of MSME enthusiasm and infrastructure.